Consolidated bioprocessing of Populus using Clostridium (Ruminiclostridium) thermocellum: a case study on the impact of lignin composition and structure. Issue 1 (December 2016) - Dumitrache, Alexandru; Akinosho, Hannah; Rodriguez, Miguel; Meng, Xianzhi; Yoo, Chang; Natzke, Jace; Engle, Nancy; Sykes, Robert; Tschaplinski, Timothy; Muchero, Wellington; Ragauskas, Arthur; Davison, Brian; et al.
Abstract Background Higher ratios of syringyl-to-guaiacyl (S/G) lignin components ofPopulus were shown to improve sugar release by enzymatic hydrolysis using commercial blends. Cellulolytic microbes are often robust biomass hydrolyzers and may offer cost advantages; however, it is unknown whether their activity can also be significantly influenced by the ratio of different monolignol types inPopulus biomass. Hydrolysis and fermentation of autoclaved, but otherwise not pretreatedPopulus trichocarpa byClostridium thermocellum ATCC 27405 was compared using feedstocks that had similar carbohydrate and total lignin contents but differed in S/G ratios. Results Populus with an S/G ratio of 2.1 was converted more rapidly and to a greater extent compared to similar biomass that had a ratio of 1.2. For either microbes or commercial enzymes, an approximate 50 % relative difference in total solids solubilization was measured for both biomasses, which suggests that the differences and limitations in the microbial breakdown of lignocellulose may be largely from the enzymatic hydrolytic process. Surprisingly, the reduction in glucan content per gram solid in the residual microbially processed biomass was similar (17–18 %) irrespective of S/G ratio, pointing to a similar mechanism of solubilization that proceeded at different rates. Fermentation metabolome testing did not reveal the release of known biomass-derived alcohol and aldehyde inhibitors that could explain observed differences in microbial hydrolytic activity. Biomass-derivedp -hydroxybenzoic acid was up to nine-fold higher in low S/G ratio biomass fermentations, but was not found to be inhibitory in subsequent test fermentations. Cellulose crystallinity and degree of polymerization did not vary betweenPopulus lines and had minor changes after fermentation. However, lignin molecular weights and cellulose accessibility determined by Simons' staining were positively correlated to the S/G content. Conclusions Higher S/G ratios inPopulus biomass lead to longer and more linear lignin chains and greater access to surface cellulosic content by microbe-bound enzymatic complexes. Substrate access limitation is suggested as a primary bottleneck in solubilization of minimally processedPopulus, which has important implications for microbial deconstruction of lignocellulose biomass. Our findings will allow others to examine differentPopulus lines and to test if similar observations are possible for other plant species.